2014
DOI: 10.1111/jspn.12071
|View full text |Cite
|
Sign up to set email alerts
|

Childhood obesity prevention: a review of school nurse perceptions and practices

Abstract: Efforts are needed to develop and implement interventions and policies to modify those perceptions that may promote school nurse active engagement in COP practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 55 publications
2
11
0
2
Order By: Relevance
“…The Norwegian national guidelines appeared to be challenging to implement among staff in primary health care (Nordstrand, Fridlund, & Sollesnes, 2016;Riiser, Londal, Ommundsen, Misvaer, & Helseth, 2015). There is limited research on the implementation of guidelines to combat obesity; however, barriers to such interventions in primary health care have been reported (Quelly, 2014a;Regber, Marild, & Johansson Hanse, 2013;Steele et al, 2011). Because public health nurses are considered key personnel in the prevention, identification and treatment of overweight and obesity among adolescents, a focus group study with school nurses was conducted to learn more about the current barriers and implementation processes.…”
Section: Introductionmentioning
confidence: 99%
“…The Norwegian national guidelines appeared to be challenging to implement among staff in primary health care (Nordstrand, Fridlund, & Sollesnes, 2016;Riiser, Londal, Ommundsen, Misvaer, & Helseth, 2015). There is limited research on the implementation of guidelines to combat obesity; however, barriers to such interventions in primary health care have been reported (Quelly, 2014a;Regber, Marild, & Johansson Hanse, 2013;Steele et al, 2011). Because public health nurses are considered key personnel in the prevention, identification and treatment of overweight and obesity among adolescents, a focus group study with school nurses was conducted to learn more about the current barriers and implementation processes.…”
Section: Introductionmentioning
confidence: 99%
“…Research shows parents feel schools and school nurses have an important role, 17 , 23 although participation of school nurses in obesity management is inconsistent. 24 From the perspective of head teachers, there may be barriers to increased school involvement which need further attention before implementing a formal initiative. 25 These centre on time, academic pressures, the requirement for more expert support and better facilities and resources within schools.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that more children and families benefit when school nurses are involved in performing obesity prevention (Quelly, 2014). Table 3 describes ideas for school nurse obesity prevention involvement.…”
Section: Role Of the School Nursementioning
confidence: 99%